Réponses

Meilleure réponse !
2014-04-15T18:07:51+02:00
Salut :)

A = (z+6)² =  z² + 2 x z x 6 + 6² = z² + 12z + 36
 
                 
B = (x-8)² = x² - 2 x (x) x 8 + 8² = x² - 16x + 64
                     
C = (4y-1)² = (4y)² - 2 x 4y x 1 + 1² = 16y² - 8y + 1    
               
D = (3p+4)² = (3p)² + 2 x 3p x 4 + 4² = 9p² + 24p + 16
                  

E= (4x+7)² = (4x)² + 2 x 4x x 7 + 7² = 16x² + 56x + 49

F = (1.5b+3.4)² = (1.5b)² + 2 x 1.5b x 3.4 + (3.4)² = 2.25b² + 10.2b  + 11.56

G = (0.7+2z)² = 0.7² + 2 x 0.7 x 2z + (2z)² = 0.49 + 2.8z + 4z²

H = (1.2+y)² = 1.2² + 2 x 1.2 x y + y² = 1.44 + 2.4y + y²

J'espère t'avoir aidé(e) ! :)

2014-04-15T18:29:30+02:00
A= (z+6)²    
=z²+12z+36
               
B=(x-8)²            
=x²-16x+64
          
C=(4y-1)²              
=16y²-8x+1
      
D=(3p+4)²        
=9p²+24p+16
    
E= (4x+7)² 
=16x²+56x+49

F=(1.5b+3.4)² 
=2.25b²+10.2b+11.56

G=(0.7+2z)²
=0.49+2.8z+4z²

H=(1.2+y)² 
=1.44+2.4y+y²